Analisis Keterampilan Sosial Siswa Kelas IV di SDN 38 Sungai Ambawang Tahun 2024 (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to find out the social skills of grade IV students at SDN 38 Sungai Ambawang in 2024. This type of research uses a qualitative approach with a descriptive method. Data collection techniques use Observation and Interview. Measurement indicators were carried out on aspects of social skills in seven aspects consisting of empathy skills, communication and social interaction, controlling aggression, open attitude, helpful behavior, self-understanding, and willingness to learn. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study showed that the ability of grade IV students of SDN 38 Sungai Ambawang based on the results of observation and teacher interviews produced several data as follows: the ability to learn behavior was perfect, namely 100%, communication and social interaction aspects as much as 91%, helpful behavior aspects as much as 84%, empathy ability aspects 75%, aggression control aspects 75%, self-understanding by 75%. As well as the aspect of openness by 72%. The results are the average number of percentages of the indicators in these seven aspects.